Different sensitivities to calcineurin inhibitors between B cells responding to blood group A and B antigens. (29th January 2016) - Yamashita, M.; Tanaka, Y.; Tazawa, H.; Sakai, H.; Ohdan, H.
Abstract : Background and Objectives: We evaluated the phenotypic and functional distinction between B cells with receptors for human blood group A and B determinants in α ‐galactosyltransferase‐deficient ( GalT −/− ) mice. Materials and Methods: GalT −/− mice were immunized with human blood group A or B red blood cells (RBCs), and the anti‐A or B anti‐bodies (Abs) were determined in their sera. B cells with receptors for group A and B epitopes were identified by the use of synthetic A and B determinants. Results: The anti‐A and anti‐B Ab levels were comparably elevated in the sera of GalT −/− mice after the immunization with A/B‐RBCs. B cells bearing receptors recognizing B epitopes exhibited the CD5 dim/− CD11b + B‐1b‐cell phenotype, whereas those with receptors for A epitopes showed the CD5 + CD11b + B‐1a‐cell phenotype. Myeloid differentiation factor 88 (MyD88) levels increased in B cells with anti‐B receptors, indicating a contribution of Toll‐like receptor (TLR) signalling, whereas no such elevation was detected in B cells with anti‐A receptors. Calcineurin inhibitor (CNI) treatment prevented the elevation of anti‐A Ab levels after immunization, but did not affect anti‐B Ab levels. Conclusions: These findings indicate different sensitivities of B cells with blood group A and B antigens in the response to CNIs.